Hear We Are: Spatial Audio Benefits Perceptions of Turn-Taking and Social Presence in Video Meetings - Nowak, Kate; Tankelevitch, Lev; Tang, John; Rintel, Sean (CHIWORK 2023, 2023)
Relative to in-person meetings, conversations in video meetings have long been reported as stilted. Spatial audio in video meetings can simulate the way we hear the world by separating audio streams based on speakers’ virtual locations. We report on a within-subject experiment in which 75 employees of a global technology company completed two group survival tasks with spatial audio enabled or disabled. Spatial audio increased perceptions of interactivity, shared space, and ease of understanding. Women experienced effects for social presence while men experienced effects for turn-taking. We discuss implications for inclusion, task performance, fatigue, and future research.